Competitive mental adaptation in cyclic sports - Kuzmin, M. A.; Zarodnyuk, G. V.; Larionova, M. N. (Theory and Practice of Physical Culture, 2019)
The article analyzes the issues and promises of the differential sport psychology, a new research discipline; considers competitive mental conditioning tools applicable in the cyclic sports; offers a set of the individual competitive adaptability rating criteria for sports on the whole and the cyclic sports in particular; and analyzes benefits of the new competitive mental adaptation model that applies the subjective and objective sets of factors and criteria. The objective competitive adaptability factors include the competitive conditions and social traits of the athletes; and the subjective competitive adaptability factors include the emotional balancing, volitional and motivational personality qualities, plus the motivations-specific missions. Furthermore, the article offers the sets of subjective and objective adaptation rating criteria. The subjective adaptation rating criteria generally include the competitive environment assessments; prestart mental conditions; and the competitive success forecasts; and the objective adaptation criteria generally include the intellectual capacity rate and competitive adaptability rate. The study data on the competitive adaptability in cyclic sports may be beneficial for the precompetitive and competitive mental conditioning technologies and tools.